ORAL AND DENTAL HEALTH KNOWLEDGE AND ATTITUDES AMONG OBSTETRICIANS: A CROSS-SECTIONAL SURVEY - Smadi, Leena (Journal of Postgraduate Medical Institute, 2018)
Objective: To determine the oral and dental health knowledge and attitudes among Jordanian obstetricians. Methodology: A cross-sectional study was performed on Jordanian obstetricians who participated in three conferences held in Amman, from August 2016 to May 2017. A specific questionnaire was used probing socio-demographic characteristics, knowledge on selected oral health issues and attitudes toward continued medical education on oral health. A total of 721 questionnaires were analysed using SPSS version 20 for Windows. Results: The respondents were 69% female, with a median age of 45.3 years. None of the responding obstetricians had attended a special course regarding oral health and only 0.4% had attended lectures related to oral health. A total of 96 (13.3%) obstetricians had read at least one scientific article related to oral and dental health in the last 5 years. The average oral health knowledge score was 44%, average knowledge score for obstetrics-related dentistry was 47% and dentistry related to systemic diseases was 57%. The average overall knowledge score was 49%. Regarding attitude towards oral health, only 37% of obstetricians agreed that oral health care is a high priority during pregnancy, while only 23% considered that treatment of dental disease during pregnancy would affect obstetrical outcomes and considered referring their patients to a dentist for treatment during pregnancy. Conclusion: Data from this study demonstrated decreased knowledge of oral and dental diseases among practicing obstetricians. Their attitudes toward oral health and dental care were poor reflecting one of the causes for their deficient knowledge.